Algorithm of Rainwater Accumulation Load Estimation - Mackūnas, Artūras; Valentinavičius, Saulius (Jaunųjų mokslininkų darbai, 2018)
The paper presents methodology of estimating rainwater load accumulation for a discrete-structural model. According to it an algorithm for estimating rainwater accumulation loading has been developed. This algorithm evaluates the geometrically nonlinear structural model deformation process. The geometrically nonlinear variation of the structural model is based on iterative calculations of the discrete model, considering the deformations of this model due to the effect of rainwater accumulation. A discrete model that conforms the calculation of the first loading iteration was provided. In addition, after the iterative calculation, a secondary model that takes into account the change of initial structure’s geometry was given.
Keywords: GNL modelling; structural analysis; actions on structures; rainwater accumulation